2015
DOI: 10.1136/bmjopen-2014-006950
|View full text |Cite
|
Sign up to set email alerts
|

25 mg versus 50 mg dose of rectal diclofenac for prevention of post-ERCP pancreatitis in Japanese patients: a retrospective study

Abstract: ObjectivesThe aim of the present study was to assess the appropriate administration dose of non-steroidal anti-inflammation drugs to prevent pancreatitis after endoscopic retrograde cholangiopancreatography (ERCP). Importantly, the 100 mg dose of diclofenac recommended in Western countries has not been permitted in Japan.DesignA retrospective study.SettingsA single centre in Japan.ParticipantsThis study enrolled patients who underwent ERCP at the Department of Gastroenterology, Osaka Saiseikai Senri Hospital, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 27 publications
0
9
1
2
Order By: Relevance
“…The results suggested that there was no significant difference in the incidence of PEP between patients who received 25-mg and 50-mg diclofenac [2/22 (9.1%) vs. 0/29 (0%), respectively; p=0.101] ( 9 ). Another retrospective study by Yoshihara et al comparing the use of a 25-mg or 50-mg rectal dose of diclofenac to prevent PEP reported that the incidence of PEP in the 25-mg group was significantly higher than that in the 50-mg group [28/84 (33.3%) vs. 11/71 (15.5), respectively; p=0.018]; this result was also found using a multivariate analysis (OR=0.35; 95% CI=0.11-0.70; p=0.007) ( 13 ). However, this study had a limitation: the baseline patient characteristics, including sex, age, and BMI were not comparable between the 25-mg and 50-mg groups.…”
Section: Discussionmentioning
confidence: 67%
“…The results suggested that there was no significant difference in the incidence of PEP between patients who received 25-mg and 50-mg diclofenac [2/22 (9.1%) vs. 0/29 (0%), respectively; p=0.101] ( 9 ). Another retrospective study by Yoshihara et al comparing the use of a 25-mg or 50-mg rectal dose of diclofenac to prevent PEP reported that the incidence of PEP in the 25-mg group was significantly higher than that in the 50-mg group [28/84 (33.3%) vs. 11/71 (15.5), respectively; p=0.018]; this result was also found using a multivariate analysis (OR=0.35; 95% CI=0.11-0.70; p=0.007) ( 13 ). However, this study had a limitation: the baseline patient characteristics, including sex, age, and BMI were not comparable between the 25-mg and 50-mg groups.…”
Section: Discussionmentioning
confidence: 67%
“…[ 41 42 ] Prior research had suggested that administration of NSAIDs may significantly reduce the risk of acute pancreatitis after retrograde endoscopic cholangiopancreatography, which was proposed to be caused by activation of chemokines after endoscopic maneuvers. [ 41 42 ] A recent study also showed that methotrexate may reduce inflammation-related cytokine levels in acute pancreatitis[ 43 ] and relieve disease progression. Moreover, methotrexate had been used as an alternative treatment in azathioprine and 6-mercaptopurine induced pancreatitis in patients with inflammatory bowel disease.…”
Section: Discussionmentioning
confidence: 99%
“…En ninguno de ellos se observaron diferencias ni en la incidencia ni en la gravedad de la PPC con dosis altas vs. estándar 88,89 . Algunos estudios (en su mayoría asiáticos) que han utilizado dosis bajas de AINE (diclofenaco 25-50 mg e indometacina 50 mg) también han demostrado un efecto positivo en la prevención de pancreatitis [90][91][92][93] . En un estudio retrospectivo que incluyó 155 pacientes, se encontró que la PPC fue menor en el grupo que recibió 50 mg de diclofenaco comparado con el grupo de 25 mg (15.5 vs. 33.3%, p = 0.018; OR: 0.27, IC 95%: 0.11-0.70, p = 0.007) 93 .…”
Section: Profilaxis Farmacológica Antiinflamatorios No Esteroideosunclassified
“…Algunos estudios (en su mayoría asiáticos) que han utilizado dosis bajas de AINE (diclofenaco 25-50 mg e indometacina 50 mg) también han demostrado un efecto positivo en la prevención de pancreatitis [90][91][92][93] . En un estudio retrospectivo que incluyó 155 pacientes, se encontró que la PPC fue menor en el grupo que recibió 50 mg de diclofenaco comparado con el grupo de 25 mg (15.5 vs. 33.3%, p = 0.018; OR: 0.27, IC 95%: 0.11-0.70, p = 0.007) 93 . Debido a que el beneficio parece ser dependiente de la dosis y que no hay diferencias en la tasa de eventos adversos con dosis bajas vs. estándar, la dosificación más recomendable continúa siendo de 100 mg.…”
Section: Profilaxis Farmacológica Antiinflamatorios No Esteroideosunclassified